IEEE Middle East Conference on Antennas and Propagation (MECAP 2010) 2010
DOI: 10.1109/mecap.2010.5724195
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body shape and gender on wireless Body Area Network on-body channels

Abstract: Technological advancements have made possible the emergence of Body Area Networks (BANs). There are numerous on-body channel characterizations in the literature performed on a phantom or a single human subject. In this paper, using multiple subjects, we consider the effect of body shape and gender on the on-body channel. A characterization of a narrowband on-body to on-body channel among different subjects is presented. The paper investigates the relationship between the propagation and the subject's physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Developing propagation models is a key challenge because of the complexity of body structure (skin, bone, liquid) and especially because of the high degree of activity during rehabilitation exercises. Indeed, Franco et al [45] showed that even small involuntary movements along with respiration can cause significant signal fading. Beside the effect of human body on the wireless transmission, the adverse biological effect of radio transmissions on human body must be investigated too.…”
Section: Body Impact On Signal Propagationmentioning
confidence: 99%
“…Developing propagation models is a key challenge because of the complexity of body structure (skin, bone, liquid) and especially because of the high degree of activity during rehabilitation exercises. Indeed, Franco et al [45] showed that even small involuntary movements along with respiration can cause significant signal fading. Beside the effect of human body on the wireless transmission, the adverse biological effect of radio transmissions on human body must be investigated too.…”
Section: Body Impact On Signal Propagationmentioning
confidence: 99%
“…Di Franco et al [4] showed that the shape of human body is an additional critical parameter in channel models. However, despite of these evidences, until now none of the LQE approaches presented in the literature have considered including some property that takes into account the effects of operating near the human body.…”
Section: Related Workmentioning
confidence: 99%
“…This fact can lead to changes in the quality of the links, affecting their reliability [2], [3]. Voluntary and involuntary movements cause shadowing, which affects the performance of the links; moreover, the shadow effect due to different body shapes has much influence in the path loss and in the distorted received signal [4].…”
Section: Introductionmentioning
confidence: 99%
“…The IEEE 802.15.6 standard [1], which is designed to address the communication in WBAN, organizes the nodes in a star topology or eventually in a two-hop extended star topology, where the hub and the node communicates using a relay node. The link reliability depends on the channel propagation conditions between transmitter and receiver, which is strongly dependent on the human mobility and on the node locations [2]. Considering that healthcare is one of the promising area of WBANs applications, a reliable and energyefficient data communication has to be provided.…”
Section: Introductionmentioning
confidence: 99%
“…• How can energy efficiency and network lifetime be maximized? The idea of this paper is to use the experimental data collected during daily activities to understand the characteristics of the wireless links in WBAN environment which is strongly influenced by the voluntary and involuntary movement [2]. The information gained from this analysis will allow us to evaluate link layer parameters which can help in designing network architecture, Medium Access Control (MAC) and routing protocols.…”
Section: Introductionmentioning
confidence: 99%